Penerapan Intervensi Pursed-Lips Breathing Meningkatkan Arus Puncak Ekspirasi pada Pasien Penyakit Paru Obstruksi Kronik - Sri Mulati Nendah Agreta; Fitrian Rayasari; Abdu Rahim Kamil (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the magnitude of the effect of pursed-lip breathing (PLB) exercises on increasing the highest flow achieved by maximal expiration peak expiratory flow (APE) in COPD patients at Jakarta Islamic Hospital Cempaka Putih based on the latest research results (evidence-based Nursing Practice). This study uses a quantitative method with a type of quantitative experimental research with a quasi-experimental approach. The results showed that the results of APE measurements before and after PLB breathing exercises to male COPD sufferers at the Jakarta Islamic Hospital showed that, in general, the effects of APE before and after PLB breathing exercises on Day-1 were 278.3 liters or minutes and general after PLB Day-1 breathing exercise was 290.0 greater. From the results of the T-Test experiment, it can be interpreted that there is a significant comparison between APE before and after PLB with the number P = 0.000 or statistically in general APE before and after PLB is smaller than in general in male respondents by (290.0– 278.3 =11.7). In conclusion, age is related to the increased value of pulmonary ventilation function in COPD patients. Age may explain the increased peak expiratory pulmonary flow in COPD patients. Thus there is a significant relationship between age and an increase in the height expiratory flow (APE) value of COPD patients after receiving pursed-lips breathing intervention. Keywords: Peak Expiratory Flow, Chronic Obstructive Pulmonary Disease, Pursed-Lip Breathing